STUDY OF THE FREQUENCY OF Malassezia pachydermatis IN DOGS WITH EXTERNAL OTITIS IN RIO GRANDE DO SUL STATE/BRAZIL - Nascente, Patrícia da Silva (2010)
External otitis is a common auditory meatus infirmity diagnosed in dogs and cats sent to veterinarian clinics. The etiology varies according to combinations of predisposing, primary and perpetuating factors, responsible for the disease. Malassezia pachydermatis is considered a normal inhabitant of the skin and can occasionally become an opportunistic pathogen of the external canal of dogs and cats. This study aimed to investigate the presence of M. pachydermatis in canine external otitis. The presence of yeast in external otitis of dogs sent to 168 veterinary hospitals in the Federal Universities of Rio Grande do Sul and Pelotas, as well as to clinics and private kennels was investigated. The sampling was performed with a sterile swab moistened with saline solution, rubbing it in the ear canal. Direct examination was performed from swabs of the collected material, stained by Gram method and examined under optical microscopy (1000X). It was seeded on Sabouraud Dextrose Agar with chloramphenicol and incubated at 32°C for up to ten days when the yeasts were identified. From the 168 cases of external otitis, M. pachydermatis was isolated in 139 (82.7%) cases. In this study, there was no difference regarding gender and age of the animals. The frequency of isolation in samples with positive scores on direct examination was significantly higher (p <0.05) than in samples with negative score. It was verified that there is a seven times-higher probability of isolating M. pachydermatis from samples with positive direct examination. It was concluded that M. pachydermatis is commonly isolated in canine external otitis cases, without significant difference in relation to sex and age. Animals with ear shifts (eg. English Cocker Spaniel) are more affected by external otitis; however, there is no difference in proportion of the number of isolation of M. pachydermatis among the races.KEYWORDS: dogs, external otitis, malasseziosis, M. pachydermatis.